The Influence of Competence and Work Environment on Employee Performance at PT. Kendali Bumi Semesta - Wulandari, Devia; Hasanah (GoAcademica Research & Publishing, 2025)
This research seeks to explore and assess the effects of competency and a structured work environment on employee skills at PT Kendali Bumi Semesta, both separately and in combination. A quantitative method with an associative research design is utilized, incorporating primary and secondary data collected through surveys distributed to 40 respondents. The data gathered is then compiled and analyzed as a saturated sample. The analytical process includes instrument evaluation, such as reliability and validity tests, along with classical assumption assessments, covering normality, heteroscedasticity, and multicollinearity tests. Furthermore, the data is examined through multiple linear regression analysis and the coefficient of determination, while hypothesis verification is carried out using t-tests and F-tests. The results indicate that employee performance is significantly and positively impacted by both competency and the work environment, whether considered individually or collectively.